1985
DOI: 10.1046/j.1537-2995.1985.25686071434.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and pathogenetic considerations in transfusion‐related acute lung injury

Abstract: Transfusion-related acute lung injury (TRALI) is an infrequent but life-threatening complication of hemotherapy. The findings in 36 cases are described. The typical clinical presentation includes acute respiratory distress characterized by hypoxemia and fulminant pulmonary edema. The onset is usually within 4 hours of transfusion and is accompanied by hypotension. In most patients (81%), recovery is rapid and complete. In 89 percent of cases, granulocyte or lymphocytotoxic antibodies are found in the serum of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
883
5
30

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 768 publications
(936 citation statements)
references
References 26 publications
18
883
5
30
Order By: Relevance
“…149,150 Although the presentation of TRALI is similar to ALI/ARDS with acute onset of dyspnea, bilateral infiltrates, and respiratory failure, resolution of TRALI is usually rapid (within 96 hours) and mortality is low (< 10%). 151 TRALI is thought to be mediated primarily by neutrophils. Because TRALI usually occurs in patients undergoing surgery or admitted to the intensive care unit, ''a two-hit'' hypothesis has been proposed for the pathogenesis.…”
Section: Alcohol Abusementioning
confidence: 99%
See 1 more Smart Citation
“…149,150 Although the presentation of TRALI is similar to ALI/ARDS with acute onset of dyspnea, bilateral infiltrates, and respiratory failure, resolution of TRALI is usually rapid (within 96 hours) and mortality is low (< 10%). 151 TRALI is thought to be mediated primarily by neutrophils. Because TRALI usually occurs in patients undergoing surgery or admitted to the intensive care unit, ''a two-hit'' hypothesis has been proposed for the pathogenesis.…”
Section: Alcohol Abusementioning
confidence: 99%
“…Clinical risk factors for TRALI that may lead to the first insult include recent surgery, sepsis, trauma, massive transfusions, hematologic malignancies, and cardiac disease. [150][151][152] The second insult is thought to be directly related to the blood product transfusion and leads to activation of the primed neutrophils with resultant pulmonary capillary leakage and noncardiogenic pulmonary edema. There are two primary theories as to the pathophysiology of the neutrophil activation.…”
Section: Alcohol Abusementioning
confidence: 99%
“…However, there are two predominant hypotheses suggested, both of which result in increased permeability of the pulmonary capillary endothelium and non-cardiogenic, protein-rich pulmonary edema. The first is the antibody-antigen hypothesis 7 wherein donor antibodies in the transfused component recognize cognate antigens on recipient leukocytes. As a result, recipient neutrophils are activated and sequestered within the pulmonary capillaries.…”
Section: Discussionmentioning
confidence: 99%
“…Even with these favourable outcomes, mortality is still 5-10%. 7,18 According to data reported by the Canadian Blood Services at the Canadian Consensus Conference, mortality from TRALI was 17%. 19 Data from the Food and Drug Administration evaluating transfusion related fatalities from 2001 to 2003, 19 showed that TRALI had emerged as the leading cause of transfusion-related death accounting for 16.3% of transfusion deaths followed by ABO incompatibility and bacterial contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Two pathophysiological mechanisms have been proposed for TRALI. In the first, named the antibody hypothesis, the pathogenesis of TRALI is related to the infusion of donor antibodies that recognize leukocyte antigens in the transfused host (1,(4)(5)(6)(7)(8)(9)(10). According to the second hypothesis, called the two-hit or twoevent model, neutrophils of recipient origin must be primed by a pre-existing clinical condition.…”
mentioning
confidence: 99%